Fault Handling Methods and Comparison for Different DC Breaker Topologies and MMC Topologies of the HVDC System. (7th February 2018) - Jiang, Xu; Bakran, Mark-M.
Abstract : The HVDC system has many significant benefits and is widely used around the world. The protection of HVDC system is always an issue, which should be solved. This paper presents the working principle of different protection schemes. The advantages and disadvantages of these protection schemes are also introduced. In order to solve the HVDC fault, two protection strategies are proposed. One design focusses on the topologies of the HVDC breaker in the HVDC line, such as all-solid HVDC breaker, resonant HVDC breaker, and hybrid HVDC breaker. The other design is from the viewpoint of converter topology, which has two types. One type generates the counter-emf in arms, such as full bridge MMC, hybrid MMC, and clamp-double MMC. The other type cuts off the current path from the AC side to the DC side, which is also introduced in this paper. Some performances of these topologies are compared, such as switching time and efficiency.